2020
DOI: 10.1108/intr-05-2019-0205
|View full text |Cite
|
Sign up to set email alerts
|

Value co-creation in firm sponsored online communities

Abstract: Purpose The purpose of this paper is to explore enablers and constraints in value co-creation in sponsored online communities, and to identify firm roles in shaping value co-creation. The structured analysis is translated into strategies for practitioners and for guiding future research. Design/methodology/approach The authors systematically review and synthesise the literature to develop a comprehensive model of value co-creation. Findings The literature review findings have led to the identification of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 118 publications
(284 reference statements)
1
32
0
Order By: Relevance
“…Likewise, one should consider encouraging participation of subject matter specialists and researchers, providing them with incentives such as remuneration for time spent, capacity-building opportunities, and career advancement/promotions (Bitzer, 2016). Priharsari et al (2020) also conclude that such a reward system is essential to co-create value, when organisations seek to connect their workforce via online networks.…”
Section: The Design and Facilitation Of An Effective Knowledge Sharing Systemmentioning
confidence: 93%
“…Likewise, one should consider encouraging participation of subject matter specialists and researchers, providing them with incentives such as remuneration for time spent, capacity-building opportunities, and career advancement/promotions (Bitzer, 2016). Priharsari et al (2020) also conclude that such a reward system is essential to co-create value, when organisations seek to connect their workforce via online networks.…”
Section: The Design and Facilitation Of An Effective Knowledge Sharing Systemmentioning
confidence: 93%
“…Recent studies have also examined user behavior and interaction in VCCs (Di Vincenzo et al, 2020;Olmedilla et al, 2019). In terms of evaluation feedback, previous studies (Kruft et al, 2019;Priharsari, Abedin, & Mastio, 2020;Saez-Rodriguez et al, 2016) have shown that idea ratings and associated scores can predict the likelihood of idea adoption. In addition, sentiment analysis of user reviews has shown that the number of positive reviews is positively related to idea quality, endorsement, and subsequent adoption in VCCs (Antons, Grünwald, Cichy, & Salge, 2020;Q.…”
Section: Idea Adoption In Crowdsourcing Communitiesmentioning
confidence: 99%
“…Various studies also confirm such behaviour within the customer-to-customer context. For example, they help disseminate information (Priharsari et al , 2020), recommend the brand to fellow associates (Casaló et al , 2011; Muñiz and Schau, 2005), persuade consumers to purchase the product (Kozinets et al , 2010), create ongoing relationships with other members (Frasquet-Deltoro et al , 2019; Andersen, 2005), empathise with other members (Schau et al , 2009) and make these consumers feel a part of the brand (McAlexander et al , 2002). In the context of brand communities, several authors have found that fellow members help other members probably because they share a common interest (i.e.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…The internet has opened up the platform of online communities for an unprecedented level of customer-to-customer interactions (Akar et al , 2019; Priharsari et al , 2020; Casaló et al , 2011). Studies support that consumers are increasingly using social media to complain (Hassan and Casaló, 2016), e.g.…”
Section: Introductionmentioning
confidence: 99%